Некоторые оценки пищевых продуктов быстрого приготовления - Shchukin P. O., Vasilyev A. S. (Science and education: future development, 2018)
fast food products are innovative, their production is developed abroad and is developing in Russia. It is necessary to increase the attention to the quality and safety of such products.
Keywords: продовольственная безопасность; пищевые продукты; food; food security; пищевые ингредиенты; food ingredients; продукты быстрого приготовления